Scarred Heart: A Case Series - S, Huzairi; SZ, Nada (International Journal of Human and Health Sciences (IJHHS), 2019)
Introduction: As of February 2018, around 900,000 Rohingyans have fled to Bangladesh to seek refuge – 80% of which were women and children.1 From satellite analyses, at least 288 villages were destroyed by fire in northern Rakhine since August 2017.2 As a tertiary medical facility catering to these refugees, the Malaysian Field Hospital (MFH) has attended to a myriad of diseases both physical and mental. The most challenging yet are burn injuries with deformities. Case 1: As a result of being torched alive, a Rohingyan woman was left with facial burns that caused visual and eating difficulties. Her scars had disfigured her so badly that her own children were terrified to look her in the face. Nonetheless, she persevered through her daily living. Case 2: A young boy who lost his father in a military attack sustained burn injuries to his left hand while escaping his burning house. As a result, he sustained a fixed deformity and total loss of function to the hand. Surgical intervention is due, however functional recovery is slim. Case 3: A young girl who sustained permanent contractures to her left foot came for treatment with MFH after many years of living with the disability. Fortunately for her, MFH was able to offer surgical intervention so she was able to regain function of her left foot. Discussion & Conclusion: While many are aware of the world’s fastest-growing humanitar ia n crisis, its origin, details and aftermath are scantily exposed. Burmese journalists have been pressured and their press freedom undermined by bureaucratic threats, budget constraints and difficult visa approvals for on-site reporting in Bangladesh.3 Volunteers should therefore share their experiences to raise awareness on the dire situation faced by refugees. However, while social media serves as a great platform to spread awareness, one has to be mindful of the refugee’s privacy and consent should be sought especially when photos and identities are shared. International Journal of Human and Health Sciences Supplementary Issue: 2019 Page: 56